The Relationship Between Soil Nitrogen Content and Soil Magnetic Susceptibility in UHO Agricultural Land - Wa Ode Fatima; Asni Asni; Wa Ode Findi Asnalda Yfandi; Wa Ode Nur Asmi Taporanggi; Wa Sina; Pratiwi Nur Aisyah; Risna Risna (Jurnal Pijar MIPA, 2026)
Soil plays an important role in supporting agricultural productivity through the availability of nutrients, particularly nitrogen, which affects plant growth and soil fertility. This study aims to determine the relationship between soil nitrogen content and soil magnetic susceptibility on agricultural land at Halu Oleo University (UHO) planted with corn, long beans, and chili peppers. Soil samples were collected at depths of 0 cm and 30 cm. Nitrogen content was analyzed using a spectrophotometer, while magnetic susceptibility was measured using an MS2B-type susceptibility meter. The results showed that both nitrogen content and soil magnetic susceptibility were higher in the surface layer and decreased at 30 cm. This indicates a relationship between soil nitrogen content and soil magnetic properties. In conclusion, nitrogen content influences variations in soil magnetic susceptibility. This study contributes to the development of a rapid, non-destructive alternative method for assessing soil fertility in agricultural land.